Investigation of 6-8. Grades secondary school students of the sun protection behaviors in Sakarya Province [Sakarya ilinde bulunan 6-8. Sınıf ortaokul öğrencilerinin güneşten korunma davranışları] - ERGÜN, AYŞE (Gulhane Military Medical Academy, 2016)
Background and objective: Transtheoretical Model (TTM), which encompasses sensitive instruments that measure an individual’s cognitive and behavioral processes, that individual’s self-confidence with respect to making a change, the perception of the decision to change, and the factors that make change difficult. The aim of the present study was investigated in an adolescent population, the relationship of sun protection behavior and gender, age, economic level and skin type. Materials and methods: The study sample comprised students enrolled in two private and a public school in the province of Sakarya, a total of 1,060 elementary school 6th-8th grade students of 2011. The instruments were administered to a total of 900 adolescents. The data were collected with sun protection scales based on the TTM. The Chi-square, Independent samples t test, ANOVA and descriptive statistics were used the data analysis. Results: There was more significant progress in 12 ages, girls and sensitive skin type of the sun protection stages of change according to others (p < 0.05). The sunscreen use stage was associated with female gender than boys and best economic levels than of the low-middle income groups were statistically significant (p <0.05). (p < 0.05). Mean scores of the girls and 12 age were found to be significantly higher in self-efficacy and perception of pros according to boys and 14 years old (p < 0.05). The economic levels higher than the medium-low income group and was statistically significant protection self-efficacy and perception of pros scores of (p <0.05). It was determined that the average perception of cons score was statistically significantly lower the girls and sensitive skin types according to the others groups (p <0.05). Conclusion: Gender, age, economic level and skin type appear to be important factors affecting sun exposure habits and sun protection behaviors among Turkish adolescent. Especially, it need to be improved in sun protection behaviors of the male, higher age 13, low economic level and dark-skinned adolescents. © GATA.
Keywords: Adolescent; Behavior change; Sun exposure; Sun protection; Transtheoretical model